FREQUENCY OF RH-D NEGATIVE & WEAK D IN PAKISTANI POPULATION - Muhammad Usman et al (Baqai Journal of Health Sciences)
Introduction:The Rh blood group system is one of the most polymorphic and immunogenic blood group systems in humans. The expression of its antigens is complex, among that Rh-D antigen is the most important antigen because of its high immunogenicity. Molecular genetic of RHD gene revealed that weak D antigen is a Rh-D phenotype that possesses less numbers of D antigen epitopes on surface of red cells. These individuals usually labeled RhD -ve by conventional testing but when transfused to RhD –ve person, it can elicit antibody production. Variableincidence of weak D worldwide,lack of awareness, proper data & multi-ethnic population of our country propelled to analyze it. Material and Methods:A cross-sectional study conducted from August 2012 to August 2014. Around 48,228 healthy blood donors were tested for RhD factor. Commercially available monoclonal anti-D sera were used to detect Rh-D factor status. Individuals found negative with saline anti-D, were further investigated for weak D antigen by using indirect Coomb’s technique (IAT). Results:Among 48,228 healthy blood donors, 44853 (93%) were Rh-D factor positive while 3375 (7%) were Rh-D factor negative. Among these, 3375 Rh-D factor negative individuals 27 (0.8%) were found to be weak D positive. Conclusion: Although frequency of weak D does not came high among our donors but is still significant enough to advocate testing of weak D in routine for all Rh –ve donors & pregnant women in order to avoid consequences of anti-D allo-immunization which can lead to serious hemato-pathological problem.